Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray Terhadap Pemahaman Konsep Matematika - Laili, sri (journal of residu, 2019)
Understandingmathematicalconcepts is an important aspect of mathematcs learning. Howeverr, that fact that understands themmathematical concepts of students in class VIII of SMP Negeri 3 Pariaman is still low. Observations show students during the laerning process5are still less active and consider mathematcs learning as a difficult lesson. One efforttto improve studentsuunderstnadinggof mathemticalgconcepts is to implement learning models that3can facilitate and increase student participation and provide opoprtunitissfor studentsgto build their own knowldge. The model that can be used is the Two Stay Two Stray type cooperative learning model. This type of research is quasi-experimental and descriptive with a Randomized Control-Group Only Design study design. The study population was grade VIII students of SMP 3 Pariaman academic year 2018/2019. The sample was class VIII.1 as the experimental class and class VIII.5 as control class. The instrument in this study was a test of understanding mathematical concepts. The final test was analyzed using the t-test. Based on the final test analysis6obtained P-value = 0.025 less than α = 0.05, meaning that understanding the mathematcal conceptoof students lerning with the Two Stay Two Stray type learning model is bettertthan understandinghthe mathmatical concepts of studnts learning with direct learninggmodels